A new soil microcosm to evaluate the Cd, Cu and Pb biosorption by Absidia cylindrospora. Issue 4 (15th June 2022) - Benjelloun, Ilham; Garon, David; Heutte, Natacha; Leleyter, Lydia; Baraud, Fabienne
Abstract: Fungi could be considered as an effective tool for treating metal pollution in soils because of their metal tolerance and biosorption capacity. While most of biosorption studies intended for bioremediation trials are carried out in liquid medium, this study presents the development of a new type of soil microcosm, designed to evaluate the fungal biosorption of metals in a solid medium. The research focused on the bioaugmentation with the fungus Absidia cylindrospora of a soil artificially contaminated by metals (Cd, Cu, and Pb). Soil microcosms were performed in layers, and a separation technique including a centrifugation step was developed. The results showed that the centrifugation step does not cause the leaching of metals from the soil. The developed procedure allows to effectively separate the mycelium from the soil at the end of the experiment. It leads to an accurate evaluation of the metal accumulated by the fungus, by better estimating the bioaccumulation factor (BAF) which was superior to 1 for the metals studied. In addition, Absidia cylindrospora was viable after 30 days experiment, and able to biosorb considerable amounts of the metals studied from the contaminated soil; it accumulates 171 mg.kg −1 of Cu, 146 mg.kg −1 of Cd and 119 mg.kg −1 of Pb. These results confirm the ability of the fungal strain to be used for bioremediation studies.